Female foeticide - Dixit, Dhruv; Sharma, Tara (Jaipur : Pointer Pubs., 2012)
Papers presented at the National Seminar: "Female Foeticide : a Social Curse".
Includes bibliographical references.
Keywords: Female feticide -- India -- Congresses; Female infanticide -- Social aspects -- India -- Congresses; Abortion -- Law and legislation -- India -- Congresses; Sex discrimination against women -- India -- Congresses